"Змійові" вали Переяславщини: характеристика просторової конфігурації - Вовкодав, С. (Український історичний збірник, 2018)
У статті розглянуто проблему просторових особливостей системи «змійових» валів Переяславщини. Систематизовано різнотипну інформацію щодо розташування, розмірів та стану збереження даного типу пам’яток. Зважаючи на своєрідну структуру системи переяславських «змійових» валів, до якої входять три відмінні між собою складові, аналіз просторових характеристик здійснювався окремо для кожної з них: Великого, Малого та Перехресного валу. Під час визначення локалізаційних особливостей згаданих об’єктів були використані як раніше відомі дані, так й інформація, отримана безпосередньо автором у ході польових досліджень. Зокрема, результати GPS-позиціонування всіх видимих сегментів насипів. Окрім цього, для визначення первинного місця розташування зруйнованих відрізків валів, використаний комплексний аналіз різного типу джерел у поєднанні з обстеженням даних дистанційного зондування Землі. Такий підхід дозволив відтворити просторову конфігурацію системи «змійових» валів окресленого регіону, яка максимально наближена до первинної. На підставі отриманих результатів, у публікації поданий опис особливостей розташування, протяжності та стану збереження кожної складової даної оборонної системи. Окрема увага автора спрямована на походження терміну «змійові», проаналізовано декілька версій виникнення цієї назви. Serpent’s wall is one of the most widespread types of archaeological sites of the Middle Dnieper. These types of earthworks are also located in the Pereiaslav region. Here they form an integral system, covering from the North-East and East the territory between the rivers Trubizh, Supiy and the Dniper. Although they have been repeatedly the object of study of many researchers, most works contain mostly partial data on their spatial characteristics. Much of the previously received information in general has lost relevance in the context of the trends of new research. Now there is a need to prepare a review, which will systematize and generalize information about the localization, configuration, condition of preservation and size of the serpent’s wall. The analysis of spatial features allows us to find out the peculiarities of the interconnection of these earthworks with the landscape and the settlement structures of the region. The system of the serpent’s wall consists of three distinct components: the Great, Small and Crossroads wall. In view of specifics of their structure, the analysis of spatial characteristics was carried out separately for each of them. The data accumulated previously and the information obtained directly by the author during field research were used to determine the localization features of the above objects. GPS-positioning of all visible segments of the embankments was carried out during several expeditions. A comprehensive analysis of various types of sources and the results of the survey of remote sensing data was used for determine the primary location of the serpent’s wall. This approach allowed for precise spatial positioning of already known segments of the serpent’s wall, to discover new segments and to determine the locations of embankments, they don’t have visible signs. As a result, we reconstructed the spatial configuration of the system of serpent’s wall in the Pereiaslav region, which is most similar to the initial. Based on the results obtained, the publication covers the peculiarities of the location, extent and state of conservation of each component of this defense system. The author’s is directed special attention at the origin of the term "serpents". The article analyzes several versions of the origin of the name, and also identifies the probable reason for their creation.